2019
DOI: 10.1111/jog.14138
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of severe acute respiratory distress syndrome due to Group A streptococcus induced toxic shock syndrome in the third trimester of pregnancy‐effectiveness of venoarterial extracorporeal membrane oxygenation: A case report

Abstract: We report a case of Group A streptococcal infection‐induced toxic shock syndrome (GAS‐TSS) with severe acute respiratory distress syndrome (ARDS), successfully treated with venoarterial extracorporeal membrane oxygenation (V‐A ECMO). A 31‐year‐old woman was transferred due to high fever, continuous uterine contractions and fetal bradycardia at 31 weeks of gestation. She was in a shock status on arrival, and as fetal heart beat disappeared, we canceled the cesarean section and took priority in maternal rescue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A total of 7 case reports describing 8 patients [7–13] and 1 retrospective observational study describing 10 patients [15] were identified. In addition, 1 case report was manually searched.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 7 case reports describing 8 patients [7–13] and 1 retrospective observational study describing 10 patients [15] were identified. In addition, 1 case report was manually searched.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid progression of circulatory failure owing to STSS leads to refractory shock and finally CPA. Recently, some case reports have demonstrated the effectiveness of VA-ECMO in saving the lives of such patients [7][8][9][10][11][12][13] ; however, its efficacy remains unknown. Therefore, we collected case reports on VA-ECMO for adult patients with STSS and investigated its characteristics and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 In addition, other single case reports of ECMO in pregnancy were published, the vast majority of which reported successful outcomes. 7 , 8 , 9 , 10 , 11 , 12 The wide range of outcomes in previous reports may reflect differences in patient-level factors and specific underlying etiologies of ARDS, in addition to publication biases. We posit that the differences we found in maternal outcomes in our cohort of women who received ECMO may reflect the unbiased reporting of all cases at our institution.…”
Section: Commentmentioning
confidence: 99%
“…The largest case series we are aware of consists of 18 women (4 pregnant and 14 postpartum) 6 ; many publications are single case reports. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Although the ELSO closely monitors outcomes and complication rates among individuals receiving ECMO, they do not track pregnancy or postpartum status. 1 Therefore, the purpose of this study is to add to the literature by providing additional cases of ECMO use in obstetric patients to further support claims of safety and efficacy when used in pregnant and postpartum women.…”
Section: Introductionmentioning
confidence: 99%